Filozofia w działaniu: egzystencjalizm w doradztwie, terapiach i coachingu = Philosophy in action: existentialism in counselling, therapy and coaching - Bartosiak, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
With its focus on human existence, with its inherent search for value and meaning, the attempt to live a full and committed, free and authentic life, the philosophy of existence is an interesting doctrine for therapists, counsellors and coaches who, in their approach to man, pay particular attention to his existential crises and sufferings, but also to his freedom, his desire for self-development and his ability to make choices.
Keywords: egzystencjalizm; psychoterapia egzystencjalna; coaching egzystencjalny; doradztwo filozoficzne; existentialism; existential psychotherapy; existential coaching; philosophical counseling